Fouling deposit from chili sauce pasteurization unit - Ali, Nur Atika; Khalid, Nurul Izzah; Ab. Aziz, Norashikin; Shamsudin, Rosnah; Taip, Farah Saleena (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The formation of fouling deposit during food processing is more rapid and requires daily cleaning to ensure the quality and safety of the food products are secured. Raw materials of the food product are essential fouling factors, which food manufacturer must comprehend before processing. This paper reports a study on fouling deposit from chili sauce pasteurization. A tubular heat exchanger was applied. The chili sauce was pasteurized at flow rate of 0.712 kg/min and temperature between 90-95°C. The formation of the fouling deposit was monitored from heat transfer profile and from naked eyes observation after every one hour of the processing. The accumulation of the deposit was detected after 3 hours when the heat transfer profile was decreasing and fouling resistance profile was increasing. The chili sauce fouling deposit is categorized as carbohydrate-based fouling deposit due to the highest percentage of carbohydrate: 46.52% carbohydrate, 3.85 % fiber, 2.71% protein, 24.18% ash, 20.44% moisture and 2.28% oil.